An investigation of crosstalk between Wnt/β-catenin and transforming growth factor-β signaling in androgenetic alopecia. Issue 30 (July 2016) - Lu, Gui-Qing; Wu, Zhi-Bo; Chu, Xiao-Yan; Bi, Zhi-Gang; Fan, Wei-Xin
Abstract: Background: Wnt and transforming growth factor-β (TGF-β) signaling pathways are known to be involved in the pathogenesis of androgenetic alopecia (AGA). However, the way that Wnt and TGF-β signaling is altered in patients with AGA and whether there exists a crosstalk between them in pathogenetic process of AGA remain unclear. Objectives: To investigate the expression of Wnt and TGF-β signaling and the crosstalk between these 2 signaling pathways in AGA. Methods: Fifteen male patients with AGA were recruited for our research. Fifteen scalp specimens of the balding were collected from frontal areas, and 9 nonbalding were collected from occipital areas. We analyzed the expression and activation of downstream Wnt and TGF-β signaling molecules in both balding and nonbalding hair follicles isolated from scalp specimens. Furthermore, we evaluated the activation of Wnt and TGF-β signaling after either of them was blocked with the inhibitor in balding and nonbalding dermal papilla (DP) cells. Results: Compared with the nonbalding counterparts, the mRNA level of Wnt10a and LEF1 was decreased. But TβRI and TβRII, and the protein expression of TGF-β1 was elevated in balding hair follicles. To investigate the crosstalk between Wnt and TGF-β signaling, we used SB431542 to inhibit the TGF-β signaling in balding DP cells and found that SB431542 significantly attenuated the phosphorylation of Smad2 and Akt. However, the mRNA level of Wnt10a, LEF1, and the nuclear translocation of β-catenin was increased. On the other hand, we suppressed the Wnt signaling by XAV939 in nonbalding DP cells, which displayed that the level of β-catenin and LEF1 was significantly inhibited; however, the level of active TGF-β1 and the phosphorylation of Smad2 and Akt were up-regulated. Conclusions: These data indicate that crosstalk between Wnt/β-catenin and TGF-β signaling pathways may exist as one of the important mechanisms contributing to AGA.